Pengaruh Context-Rich Problems Berbentuk Multimedia Interaktif terhadap Keterampilan Proses Sains, Sikap Ilmiah, dan Pemahaman Konsep - Yusran Khery; Khaeruman Khaeruman (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2016)
The purpose of this study was to evaluate the effect of context-rich problems in the form of interactive multimedia on chemical students’ science process skills, scientific attitudes, and conceptual understanding in practical activities. This research is the quasi-experimental study with post test only control group design. The research sample consisted of 142 students divided into 3 groups. The 1st experimental group was treated using a context-rich problem in the form of interactive multimedia before practical activities, the 2nd experimental group used conventional rich problems, and control groups without context-rich problems. Data were collected by the science process skills observation sheets and portfolio, scientific attitude observation sheets, and conceptual understanding tests. Data were analyzed by inferential statistical methods using SPSS 15 software for windows. The results showed that the context-rich problems in the form of interactive multimedia had an effect on students' science process skills, scientific attitudes, and conceptual understanding.